Does adding extracorporeal shock wave therapy to postural correction exercises improve pain and functional disability in postpartum sacroiliac joint pain? A randomized controlled trial - Elhosary, Eman Abdelfatah Mohamed; Hamada, Hamada Ahmed; Ewidea, Mahmoud; Al-Shenqiti , Abdullah M.; Mohamed, Yassmin Essam (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
Examining the outcome of the extracorporeal shock wave therapy (ESWT) on females with postpartum sacroiliac joint pain was the aim of this study. Forty primigravida (six weeks postpartum) females with sacroiliac pain was the sample in this study. The subjects equally randomly allocated in group A and B. Group A was treated by ESWT in addition to postural correction and posterior pelvic tilting exercises. Group B was treated by the same exercise program only. Two sessions every week for four weeks were received by both groups. The measurement variables were sacroiliac pain and function level that were measured by visual analogue scale (VAS) and the back pain functional scale (BPFS), respectively. All measurements were evaluated pre and post four weeks of intervention. The within groups analysis showed a significant improvement in VAS and a significant increase in BPFS in both groups after treatment compared with baseline. Regarding between groups analyses there was a significant improvement in VAS and a significant increase in BPFS in group A compared with group B. In conclusion, both ESWT and exercise program are effective in decreasing the pain and improving the function in females with postpartum sacroiliac pain. However, by adding ESWT to exercises in the treatment program the results are better, so this combination is recommended in treatment of females with postpartum sacroiliac pain.